The Chilean national system of innovation - Benavente, José Miguel; Crespi, Gustavo (Estudios de Economía, 2016)
It may be stated that there exists, within the field of the economy, a growing consensus regarding the fact that together with capital accumulation, technological progress and its associated innovations are the central forces of the process of economic growth and increase in welfare of the countries. There does not exist any country at a world level that has experienced important increases in its level of development without consistently exhibiting a sustained increase in its endowment of machinery and equipment per worker, as well as continuous improvements in the efficiency and quality of both such capital goods and the human resources responsible for their operation. Based on the above, this research is aimed at characterizing both the processes that are determinant of the fundamental interrelationships as well as the agents responsible for the innovative phenomenon in the case of Chile.